Islamic Group Guidance with Video as The Media to Improve Students Entrepreneurship of Vocational (Universitas Negeri Semarang, 2019)
This purpose of this study is to find out the effectiveness of Islamic group guidance with videos as the media can improve the students’ entrepreneurship. The design of this experimental research, with one group pre-test – post-test design. The subject of research is of 10 students with criteria of low-or-medium entrepreneurship. The hypothesis is proven using Wilcoxon Signed Ranks Test. The result of the study shows an increase of the students’ entrepreneurship between pre-test and post-test (Z = -2.52; p < 0.01). There is a significant entrepreneurship difference between pre-test and post-test where entrepreneurship at post-test is higher than pre-test, which means the implementation of group guidance with the movie as the media can improve the student's entrepreneurship. This research emphasis that the implementation of Islamic group supervision with videos as the media is effective on improving the students’ entrepreneurship.